Shrine dedicated to Lord Hanuman - Mumbai Archive Project Team (Jio Institute, 2024)
Shrine dedicated to Lord Hanuman. Tuesdays are the busiest days, as worshippers visit the temple to pray to Lord Hanuman on Tuesdays.